The Group Final Exam with Constructivist Learning Theory as a Solution to Overcome the Situation if Students Losing Interest in Learning After the Exam - Dwiyanti, Retno (International Conference on Elementary Education, 2024)
The purpose of this study is to find ways to increase students' interest in learning after the exam. This research can be used to find suitable learning strategies for students. This research method is literary research. The research stages include identifying sources, collecting data, analyzing data, and interpreting data. This study has shown that assessment is an important activity in the world of education. Through evaluation activities, the effectiveness of an educational program can be tested for feasibility and further actions for developing that program can be determined. Group final exams based on constructivist learning theory can be used as a solution to increase students' interest in learning after the exam. Group assessment also reduces student anxiety during the final assessment process. With the new concept of final group assessment without forgetting the success indicators designed in the assessment, it can be used as a solution to increase students' interest in learning. The new concept of final group assessment also allows students to face assessments without undue anxiety because each individual can complement the other's respective strengths. The conclusion of this study is that a well-designed method of conducting constructive final exams can increase students' interest in learning. Good preparation and meeting students' needs are essential so that group final exams according to constructivist learning theory can increase students' learning interest as expected. This research is highly recommended for designing learning activities, especially final assessments, to enhance learning interest. The state of reduced interest in learning after the end of the exam can be appropriately overcome in accordance with the identified learning goals.